Identication of Variance Moleculer Genotype Commercial Oil Palm (Elaeis guineensis Jacq.) based on Random Amplified Polymorpism DNA (RAPD) Markers - Arnen Pasaribu; Lollie Agustina P.Putri; Dwi Suryanto (INSIST, 2017)
Abstract —Commercial oil palm is one of plant genotype have a inbreeding so that it will be genetic depression.  Genetic depression can cause difficulties to identification of genetic trait in palm oil, so that identification of moleculer variance is necessary to know the genetic potential of commercial palm oil to obtain initial information about genetic diversity. The objectives of this study was to find genetic diversity in commercial oil palm (E. guineensis Jacq.) by using five RAPD primers (OPC-12, OPH-12, OPC-7, OPI-20 and OPD-16). The results of this study showed that Polymorpism Information Content (PIC) was 0.338.  PCoA analysis showed that the moleculer varian was 43,72% and according to profil radial neighbour joining tree (NJtree) showed that three main groups. Keywords—Genetic Variation,Oil Palm , RAPD